Brazing of Ti alloys with Ti–Zr–Cu amorphous filler metal. (4th August 2014) - Hirose, Akio; Nojiri, Makoto; Ito, Hirotake; Kobayashi, Kojiro F.
Commercial purity titanium (CP–Ti) and Ti–10Zr alloy were brazed with amorphous 25Ti–25Zr–50Cu filler metal using argon gas shielding. To obtain high joint strengths of approximately 400MPa and more, it was necessary that no central brazed layer consisting of intermetallic compounds (Ti, Zr)Cu, (Ti, Zr)2 Cu andlor Cu2 TiZr remained in the brazed joints after brazing. To this end, the CP–Ti brazes required brazing temperatures of 1193K and more and holding time of at least 120s, in which conditions the joints were fractured in the base metal. On the contrary the Ti–10Zr joints brazed at 1153K and 1173K had joint strengths of approximately 400MPa for a holding time of 300ks and were fractured in the base metal after 600s. This difference between brazeabilities of CP–Ti and Ti–10Zr was explained by considering the microstructural evolution of the brazing filler metals during brazing using the liquidus projection of the Cu–Ti–Zr ternary system.